Resveratrol as a potential therapeutic drug for respiratory system diseases - Zhu X; Lei X; Dong W (Dove Medical Press, 2017)
Xiao-dan Zhu, Xiao-ping Lei, Wen-bin Dong Department of Newborn Medicine, The Affiliated Hospital of Southwest Medical University, Luzhou, Sichuan, People’s Republic of China Abstract: Respiratory system diseases are common and major ailments that seriously endanger human health. Resveratrol, a polyphenolic phytoalexin, is considered an anti-inflammatory, antioxidant, and anticancer agent. Thanks to its wide range of biological activities, resveratrol has become a hotspot in many fields, including respiratory system diseases. Indeed, research has demonstrated that resveratrol is helpful to relieve pulmonary function in the general population. Meanwhile, growing evidence indicates that resveratrol plays a protective role in respiratory system diseases. This review aimed to summarize the main protective effects of resveratrol in respiratory system diseases, including its anti-inflammatory, antiapoptotic, antioxidant, antifibrotic, antihypertensive, and anticancer activities. We found that resveratrol plays a protective role in the respiratory system through a variety of mechanisms, and so it may become a new drug for the treatment of respiratory system diseases. Keywords: respiratory system diseases, resveratrol, inflammation, apoptosis, oxidation